"We treat humans, not herds!": A qualitative study of complementary and alternative medicine (CAM) providers' individualized approaches to vaccination in Switzerland. (November 2019) - Deml, Michael J.; Notter, Julia; Kliem, Paulina; Buhl, Andrea; Huber, Benedikt M.; Pfeiffer, Constanze; Burton-Jeangros, Claudine; Tarr, Philip E.
Abstract: Complementary and alternative medicine (CAM) providers' roles in parents' decision-making about vaccinations for their children have only recently begun receiving research attention, despite studies showing CAM to be used by 25–50% of the population in Western countries. This article examines how CAM practitioners discuss vaccinations with parents in Switzerland, with a focus on childhood vaccinations and human papillomavirus (HPV) vaccinations. We describe how the CAM providers we interviewed (N = 17) and observed during vaccination consultations (N = 18 observations with 5 providers) employed individualized approaches to vaccination. Triangulation of qualitative evidence from interviews and observations allowed us to analyze their discourses and descriptions of experiences (i.e. what they said) and their practices in situ (i.e. what they did). Evidence gathered shows that practitioners framed vaccination decisions as choices at individual and family levels rather than focusing on public health benefits and consequences. They articulated their perspectives in terms of personal clinical experiences and parents' wishes, concerns, and contexts. Such findings challenge recurring narratives depicting CAM providers as categorically anti-vaccination and suggest that approaches to address vaccine hesitancy in clinical practice could benefit from communication and relational approaches similar to those demonstrated by participants in this study. Such approaches include taking time to understand parents' wishes, involving them in vaccination decisions, and taking their concerns seriously. Highlights: Complementary medical providers' individualized vaccine counseling in Switzerland. Complementary and alternative medical providers not categorically anti-vaccine. Ethnographic observations and descriptions of vaccine consultations. Qualitative interviews about vaccination with complementary medical providers.